Operationalising a conceptual framework for a contiguous hospitalisation episode to study associations between surgical timing and death after first hip fracture: a Canadian observational study. Issue 12 (6th December 2018) - Sheehan, Katie Jane; Levy, Adrian R; Sobolev, Boris; Guy, Pierre; Tang, Michael; Kuramoto, Lisa; Sutherland, Jason M; Beaupre, Lauren; Morin, Suzanne N; Harvey, Edward; Bradley, Nick
Abstract : Objective: We describe steps to operationalise a published conceptual framework for a contiguous hospitalisation episode using acute care hospital discharge abstracts. We then quantified the degree of bias induced by a first abstract episode, which does not account for hospital transfers. Design: Retrospective observational study. Setting: All acute care hospitals in nine Canadian provinces. Participants: We retrieved acute hospitalisation discharge abstracts for 189 448 patients aged 65 years and older admitted to acute care with hip fracture between 2003 and 2013. Primary and secondary outcome measures: The percentage of patients treated surgically, delayed to surgery (defined as two or more days after admission) and dying, between contiguous hospitalisation episodes and the first abstract episodes of care. Results: Using contiguous hospitalisation episodes, 91.6% underwent surgery, 35.7% were delayed two or more days after admission and 6.7% died postoperatively, whereas, using the first abstract only, these percentages were 83.7%, 32.5% and 6.5%, respectively. Conclusion: We demonstrate that not accounting for hospital transfers when evaluating the association between surgical timing and death underestimates reporting of the percentage of patients treated surgically and delayed to surgery by 9%, and the percentage who die after surgery by 3%. Researchers must be aware of this potential and avoidable bias as, depending on the purpose of the study, erroneous inferences may be drawn.